Effect of population densities on rubber growth and yield in Veracruz - Ortiz-Cervantes, Elías; Hernández-Cruz, José Miguel; Moctezuma-López, Georgel (Revista Mexicana de Ciencias Agrícolas, 2022)
In Mexico, the average annual yield of rubber (Hevea brasiliensis [Willd. ex A. Juss] Muell. Arg.) is less than 1.2 t ha-1, by optimizing population density is sought to increase yield and productivity. The work was carried out in the central region of the state of Veracruz. The planting arrangements 4x2, 6x3 (control), 8x4 and 10x5 m, with densities of 1 250, 556, 312 and 200 trees ha-1, respectively, were evaluated. The experimental design was randomized blocks with four repetitions and 40 trees of clone IAN-754 per experimental unit. The main variables evaluated were stem circumference, rubber yield and biomass yield. At the seventh year, it was obtained that the higher the density, the lower the percentage of trees suitable for extracting latex (stem circumference >45 cm). The circumference of the stem at the end of the period ranged between 67 and 120 cm, at a higher density there was less growth and greater number of trees suppressed. At a higher density, lower yield in grams per tree per tapping of rubber, but higher yield in kg per hectare per year, with an oscillation between 960 and 2 040 kg, were obtained. The total biomass per tree ranged from 223 to 924 kg and the total biomass per hectare between 158 and 240 t ha-1. In addition, with higher population densities, the rubber yield was higher and with 556 trees, a better balance was achieved.
Keywords: biomass; latex; planting arrangements; productivity